2007
DOI: 10.1007/s11055-007-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BT-melanin on recovery of operant conditioned reflexes in rats after ablation of the sensorimotor cortex

Abstract: An increase in corticofugal plasticity was demonstrated in adult rats after unilateral ablation of the sensorimotor cortex accompanied by intramuscular administration of low concentrations of BT-melanin solution. The result was acceleration of the process of compensatory recovery in the central nervous system, this being supported by the rapid recovery of a previously acquired operant conditioned reflex and movement of the paralyzed limb as compared with control animals. It is suggested that compensation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Different concentrations of BM have been tested by us in previous series of experiments. The concentration 6mg/ml calculated as 170 mg/kg showed to be the most effective (Gevorkyan et al, 2007;Gevorkyan et al, 2008). It had more favorable and expressed effects on nervous tissue regeneration, sprouting, and functional recovery than the higher doses of BM.…”
Section: Discussionmentioning
confidence: 93%
“…Different concentrations of BM have been tested by us in previous series of experiments. The concentration 6mg/ml calculated as 170 mg/kg showed to be the most effective (Gevorkyan et al, 2007;Gevorkyan et al, 2008). It had more favorable and expressed effects on nervous tissue regeneration, sprouting, and functional recovery than the higher doses of BM.…”
Section: Discussionmentioning
confidence: 93%
“…However, the release of neuromelanin from compromised neurons triggers microglial activation and the neurodegenerative process. Studies using BM have demonstrated that this substance does not induce microgliosis and has no toxic side effects [ 17 ]. In our study, rotenone was employed to create an experimental animal model of PD that simulates and induces symptoms akin to Parkinson’s disease, including motor and cognitive impairment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature data indicate that BM has been utilized in various physiological studies to facilitate the rapid recovery of impaired motor functions in rats following the destruction of certain CNS structures involved in the organization of the animal’s motor behavior. It has been determined that BM exhibits high biological activity and a biostimulating effect, and at low concentrations (4.5–6 mg/ml), it does not induce microgliosis or have toxic side effects [ 17 , 18 ]. BM may promote the survival of neurons in the substantia nigra in the presence of toxic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial melanin (BM) has proved to be a potent stimulator of axonal growth (Petrosyan et al 2012;Petrosyan and Gevorkyan 2013). In a previous series of experiments, BM was used to facilitate recovery processes in rats after unilateral ablation of the sensorimotor cortex that had caused paresis of limbs (Gevorkyan et al 2007(Gevorkyan et al , 2008. BM supports axonal regeneration, stimulates sprouting of nerve fibers and vascularization.…”
Section: Introductionmentioning
confidence: 99%